Biosynthesis of biotin and lipoic acid - Marquet, Andrée; Tse Sum Bui, Bernadette; Florentin, Dominique (Cofactor Biosynthesis: a Mechanistic Perspective, 2001)
The genetics and mechanistic enzymology of biotin biosynthesis have been the subject of much investigation in the last decade, owing to the interest for biotin production by fermentation, on the one hand, and for the design of inhibitors with potential herbicidal properties, on the other hand. Four enzymes are involved in the synthesis of biotin from its two precursors, alanine and pimeloyl-CoA. They are now well-characterized and the X-ray structures of the first three have been published. 8-Amino-7-oxopelargonic acid synthase is a pyridoxal 5′-phosphate (PLP) enzyme, very similar to other acyl-CoA α-oxoamine synthases, and its detailed mechanism has been determined. The origin of its specific substrate, pimeloyl-CoA, however, is not completely established. It could be produced by a modified fatty acid pathway involving a malonyl thioester as the starter. 7,8-Diaminopelargonic acid (DAPA) aminotransferase, although sharing sequence and folding homologies with other transaminases, is unique as it uses S-adenosylmethionine (AdoMet) as the NH 2 donor. The mechanism of dethiobiotin synthethase is also now well understood. It catalyzes the formation of the ureido ring via a DAPA carbamate activated with ATP On the other hand, the mechanism of the last enzyme, biotin synthase, which has long raised a very puzzling problem, is only starting to be unraveled and appears indeed to be very complex. Biotin synthase belongs to the family of AdoMet-dependent enzymes that reductively cleave AdoMet into a deoxyadenosyl radical, and it is responsible for the homolytic cleavage of CH bonds. A first radical formed on dethiobiotin is trapped by the sulfur donor, which was found to be the iron-sulfur (FeS) center contained in the enzyme, and cyclization follows in a second step. Two important features come from these results: (1) a new role for an FeS center has been revealed, and (2) biotin synthase is not only a catalyst but also a substrate for the reaction. Lipoate synthase, which catalyzes the formation of two CS bonds from octanoic acid, has a very high sequence similarity with biotin synthase. Although no in vitro enzymology has been carried out with lipoate synthase, the sequence homology as well as the results of in vivo studies support the conclusion that both enzymes are strongly mechanistically related.